The vitamin D and immunological performance: a perspective within multiple sclerosis (Research, Society and Development, 2021)
Introduction: Multiple sclerosis (MS) is a chronic, degenerative, autoimmune disease that generates inflammation in brain and spinal cord regions. The disease can affect any region of the central nervous system, with a variety of symptoms. Its causes are multifactorial, being related to genetic, behavioral, environmental, and immunological components mediated by vitamin D biochemistry. Vitamin D has a function in immune mediation in the anti-inflammatory process, in what concerns reducing the levels of inflammatory cytokines and potentiating the anti-inflammatory ones in the process of six months supplementation. Objective: To analyze the advantages of the use of vitamin D in patients with multiple sclerosis. Methodology: This is an integrative literature review. A bibliographic search of articles in the PubMed, SciELO and Medline databases was carried out from 2010 to 2020, using the descriptors: "Vitamin D", "Multiple Sclerosis" and "Immune System". Inclusion criteria included articles in English and Portuguese limited to a period of 10 years, available in full. Theses, theoretical reviews, book chapters and duplicate articles were excluded. Results: A total of nine studies were analyzed in this review. It was found in the literature, that vitamin D plays an important role in the rehabilitation process of patients with multiple sclerosis, highlighting its action in the inhibition of inflammatory mediators after the influence of continuous supplementation with vitamin D. Conclusion: Therefore, that the use of Vitamin D shows good results in the treatment and recovery of multiple sclerosis disease sufferers. However, more detailed studies are needed regarding doses and possible deleterious effects.